Biosynthesized Gold Nanoparticle Developed as a Tool for Detection of HCG hormone in Pregnant Women Urine Sample - Kuppusamy, Palaniselvam; M. M., Yusoff; Gaanty Pragas, Maniam; Natanamurugaraj, Govindan (Elsevier, 2014)
This paper presents a microencapsulation study using whey protein isolate and maltodextrin of polyphenol obtained from Orthosiphon stamineus leaves. Polyphenol content was analysed using ultra-performance liquid chromatography. Higher solid concentration leads to higher solution viscosity, bigger particle size, lower moisture content and less dented surface, which may improve particle flowability. Microencapsulation using a least amount of protein (0.05wt.%) yielded better retention of romarinic acid (82.08%), sinensetin (79.57%) and eupatorin (81.08%) than those with higher protein concentration. Meanwhile, 5.33 wt.% of maltodextrin provide the highest polyphenol retention of rosmarinic acid (82.67%), sinensetin (82.24%) and eupatorin (80.19%). The results suggest that eupatorin and rosmarinic acid are more susceptible to thermal degradation than sinensetin during spray drying. Formulation using 5.33% maltodextrin provide a better preservation of polyphenols compared to other formulations.